2018
DOI: 10.1111/hae.13608
|View full text |Cite
|
Sign up to set email alerts
|

Once‐weekly prophylaxis with 40 IU/kg nonacog beta pegol (N9‐GP) achieves trough levels of >15% in patients with haemophilia B: Pooled data from the paradigm™ trials

Abstract: Introduction Prophylaxis with replacement factor IX (FIX) reduces bleeding frequency and improves quality of life in haemophilia B patients. With prophylaxis, the likelihood of bleeding is lowered with increasing trough levels. New products with extended half‐life (EHL) can maintain high factor activity levels over prolonged periods, compared with standard FIX products. Aim To evaluate the safety, efficacy and pharmacokinetics of the new recombinant FIX EHL product, nonacog beta pegol (N9‐GP), using pooled dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Following full-text review, nine articles met the inclusion criteria ( Figure 1). These studies included EHL rFIX products, with one study of rIX-FP (IDELVION 8 ), one study of rFIXFc (Alprolix 9 ), and two studies of N9-GP (Refixia 10,14 ). Standard-acting rFIX products were also included, with two studies of rFIX (BeneFIX 13,15 ), two studies of BAX 326 (Rixubis 16,17 ), and one study of IB1001 (Ixinity 18 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Following full-text review, nine articles met the inclusion criteria ( Figure 1). These studies included EHL rFIX products, with one study of rIX-FP (IDELVION 8 ), one study of rFIXFc (Alprolix 9 ), and two studies of N9-GP (Refixia 10,14 ). Standard-acting rFIX products were also included, with two studies of rFIX (BeneFIX 13,15 ), two studies of BAX 326 (Rixubis 16,17 ), and one study of IB1001 (Ixinity 18 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the results of the adult pivotal trial were separately reported by Windyga et al 16 , the Solano Trujilo et al 17 study was excluded from further review and analysis to prevent including duplicate patients. Similarly, Oldenburg et al 14 reported pooled results from the paradigm trials, and so was excluded from further review to prevent patient duplication, as the results of the adult trial were reported separately by Collins et al 10 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…[8][9][10] Moreover, an ongoing clinical trial with recombinant FIX albumin fusion is investigating whether the dosing interval could be extended to 21 days (clinicaltrials.gov: NCT02053792). 11,[13][14][15][16] These results make such therapies significantly less distressing to the patient (particularly in the case of FIX) and are likely to improve their quality of life. 11,[13][14][15][16] These results make such therapies significantly less distressing to the patient (particularly in the case of FIX) and are likely to improve their quality of life.…”
mentioning
confidence: 99%
“…Despite these potential differences in extravascular distribution, all EHL FIX products have shown excellent efficacy in clinical trials. [6][7][8] Differences in extravascular distribution observed across FIX products may also be due to variances in measurement parameters.…”
Section: Optimal Trough Levels In Haemophilia B: Raising Expectationsmentioning
confidence: 99%